Diabetes Screening and Prevention in a High-Risk, Medically Isolated Border Community - Millard, Ann V.; Graham, Margaret A.; Mier, Nelda; Moralez, Jesus; Perez-Patron, Maria; Wickwire, Brian; May, Marlynn L.; Ory, Marcia G. (Frontiers in Public Health, 2017)
Introduction A project in a Texas border community setting, Prevention Organized against Diabetes and Dialysis with Education and Resources (POD2ER), offered diabetes prevention information, screening, and medical referrals. The setting was a large, longstanding flea market that functions as a shopping mall for low-income people. The priority population included medically underserved urban and rural Mexican Americans. Components of the program addressed those with diabetes, prediabetes, and accompanying relatives and friends. Background People living in the Lower Rio Grande Valley (LRGV) face challenges of high rates of type 2 diabetes, lack of knowledge about prevention, and inadequate access to medical care. Recent statistics from actual community-wide screenings indicate a high diabetes prevalence, 30.7% among adults in the LRGV compared with 12.3% nationwide. Methods A diverse team composed of public health faculty, students, a physician, a community health worker, and community volunteers conceived and developed the project with a focus on cultural and economic congruence and a user-friendly atmosphere. The program provided screening for prediabetes and diabetes with a hemoglobin A1c test. Screening was offered to those who were at least 25 years of age and not pregnant. When results indicated diabetes, a test for kidney damage was offered (urinary albumin-to-creatinine ratio). A medical appointment at a community clinic within a week was provided to those who tested positive for diabetes and lacked a medical home. Health education modules addressed all family members. Discussion The project was successful in recruiting 2,332 high-risk people in 26 months in a community setting, providing clinic referrals to those without a doctor, introducing them to treatment, and providing diabetes prevention information to all project participants. Implications for research and practice are highlighted. Conclusion This study shows that a regular access point in a place frequented by large numbers of medically marginalized people in a program designed to eliminate cultural and economic barriers can succeed in providing a hard-to-reach community with diabetes prevention services. Aspects of this program can serve as a model for other service provision for similar populations and settings.